A sustainable environmental study on clamshell powder, slag, bagasse ash, fly ash, and corn cob ash as alternative cementitious binder. Issue 1 (August 2021) - Abdullah, N O; Fakhruddin,; Bachtiar, R D W; Rusni, N K
Abstract: Concrete is one of the most commonly used construction materials, consisting of water, aggregate and cement. The use of Portland cement in the manufacture of concrete has a negative impact to the environment. Therefore, one alternative solution that can be done is to replace some of the cement content in concrete by utilizing waste such as Bagasse Ash, Fly Ash, and Corncob Ash, as a substitute material. In addition, the use of sand and gravel as aggregates can also be partial by utilizing Clamshell Powder as a partial substitute for fine aggregate and Nickel Slag as a partial substitute for coarse aggregate. This study aims to create high quality Self Consolidating Concrete (SCC) that is environmentally friendly with a simple steam curing method. The study used a tested object in the form of a 150x300 mm cylinder with the use of 3% bagasse ash, 10% fly ash, and 2% corncob ash as a partial substitute for cement, 9% Clamshell Powder as a partial substitute for sand, and 40% nickel slag that passed the 3/8 sieve and be restrained the No. 4 sieve as a partial substitute for gravel. Steam curing of the specimen was carried out at 7080 °C for 4 hours and continued with curing at room temperature until the testing time. Testing of concrete compressive strength aged 1 day is expected to produce concrete with a minimum strength of 30 MPa.